Effect of Brain Exercise on Cognitive Function in the Elderly with Dementia At the Graha Werdha Marie Joseph Pontianak - Ariyanti, Sri; Surtikanti, Surtikanti; Wahyuni, Tri; Lukita, Yenni (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
The increase in the number of elderly people in Indonesia is related to increasing health problems, including a decline in cognitive function due to the aging process. One of the disorders that occur in the elderly is dementia, which is characterized by a decrease in memory, thinking, and the ability to carry out daily activities. To prevent cognitive decline, one of the non-pharmacological interventions that can be applied is brain exercises. This study aims to determine the effect of brain gymnastics on improving cognitive function in the elderly. The type of research used in this study is quantitative research using a pre-experimental research design using a one group pretest and posttest design approach with a sampling technique, namely purposive sampling with a sample of 25 elderly respondents living in Graha Werdha Marie Joseph Pontianak. The data collection technique that will be used is the MMSE questionnaire. The intervention lasted for two weeks by providing nursing actions in the form of brain exercises for 15 minutes a day, after which an evaluation was carried out on the respondents. Data analysis using paired tests. The results showed that there was an effect of brain gymnastics on improving cognitive function in the elderly (p value 0.000). Brain exercises can be done regularly as a form of intervention in improving cognitive function in the elderly.